Recent results on heavy-ion direct reactions of interest for 0νββ decay at INFN - LNS. (September 2020) - Cavallaro, M.; Acosta, L.; Adsley, P.; Agodi, C.; Altana, C.; Amador-Valenzuela, P.; Auerbach, N.; Barea, J.; Bellone, J. I.; Bijker, R.; Borello-Lewin, T.; Boztosun, I.; et al.
Abstract: Neutrinoless double beta decay of nuclei, if observed, would have important implications on fundamental physics. In particular it would give access to the effective neutrino mass. In order to extract such information from 0νββ decay half-life measurements, the knowledge of the Nuclear Matrix Elements (NME) is of utmost importance. In this context the NUMEN and the NURE projects aim to extract information on the NME by measuring cross sections of Double Charge Exchange reactions in selected systems which are expected to spontaneously decay via 0νββ. In this work an overview of the experimental challenges that NUMEN is facing in order to perform the experiments with accelerated beams and the research and development activity for the planned upgrade of the INFN-LNS facilities is reported.